2022
DOI: 10.2196/29880
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Impact of COVID-19 on Telemedicine Utilization: Retrospective Observational Study

Abstract: Background While telemedicine has been expanding over the past decade, the COVID-19–related restrictions regarding in-person care have led to unprecedented levels of telemedicine utilization. To the authors’ knowledge, no studies to date have quantitatively analyzed both national and regional trends in telemedicine utilization during the pandemic, both of which have key implications for informing health policy. Objective This study aimed to investigate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 23 publications
1
11
1
Order By: Relevance
“…The majority of our quantitative and qualitative findings validate and extend previous work. Our results confirm the large-scale uptake of remote care that was found for other countries as well ( 17 ), though only for the tools that were necessary to enable continuation of care, which was particularly salient for videoconferencing tools, but also for e-mail, text messaging and online screening. As expected, we found that not only did the use of these necessary tools increase, so did practitioners’ competency with them.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The majority of our quantitative and qualitative findings validate and extend previous work. Our results confirm the large-scale uptake of remote care that was found for other countries as well ( 17 ), though only for the tools that were necessary to enable continuation of care, which was particularly salient for videoconferencing tools, but also for e-mail, text messaging and online screening. As expected, we found that not only did the use of these necessary tools increase, so did practitioners’ competency with them.…”
Section: Discussionsupporting
confidence: 84%
“…The advent of the COVID-19 pandemic, however, necessitated a drastic change for mental healthcare practice. Physical distancing measures forced the majority of mental health practitioners to almost instantly transfer their practice to remote modalities, leading to the large-scale use of online mental healthcare services ( 17 , 18 ). While acknowledging the great burden the pandemic and its social and physical consequences caused for both practitioners and clients, this period also offers an opportunity to investigate the lived experience of DMH tool use by a much broader group of users – both therapists and clients – than have been exposed to such tools to date.…”
Section: Introductionmentioning
confidence: 99%
“…However, no following change in the trend was evident with either model. This is not consistent with results from a previous study in the United Kingdom, where universal health coverage is provided through the National Health Service, similar to Japan [ 24 ]. When focusing on the Japanese policy strategy for telehealth from the point of view of providers, until at least 2022, telehealth has not spread widely in Japan because face-to-face consultations are more profitable for medical institutions than telehealth.…”
Section: Discussioncontrasting
confidence: 99%
“…One study found that while reduction in PTSD symptoms did not differ between telehealth and in-person conditions for participants who completed PE, participants randomized to telehealth PE demonstrated higher dropout compared to those randomized to in-person PE (Morland, Mackintosh, et al, 2020; Morland, Wells, et al, 2020). Emerging research demonstrates that the coronavirus disease (COVID-19) pandemic led to a large, rapid increase in telemedicine utilization (Rosen et al, 2021; Vogt et al, 2022); however, there are several concerns raised by this rapid adoption of telemedicine, including that not all service users can be reached by this means, as well as the lack of evidence regarding long-term impacts on therapeutic relationships and quality of care (Appleton et al, 2021)…”
Section: Recommendationsmentioning
confidence: 99%
“…One study found that while reduction in PTSD symptoms did not differ between telehealth and in-person conditions for participants who completed PE, participants randomized to telehealth PE demonstrated higher dropout compared to those randomized to in-person PE (Morland, Mackintosh, et al, 2020;. Emerging research demonstrates that the coronavirus disease (COVID-19) pandemic led to a large, rapid increase in telemedicine utilization (Rosen et al, 2021;Vogt et al, 2022); however, there are several concerns raised by this rapid adoption of telemedicine, including that not all service users can be reached by this means, as well as the lack of evidence regarding long-term impacts on therapeutic relationships and quality of care (Appleton et al, 2021) In addition to telehealth (telephone of video) delivered EBPs for PTSD, web-based self-guided versions of EBPs for PTSD have potential not only to increase ease of access to these treatments, but also to increase availability of these programs by reducing time investment for clinicians, allowing each clinician to serve more patients. Web-based EBPs adapt content from individual therapy EBPs, with therapists typically facilitating engagement by providing asynchronous (i.e., not immediate) feedback via phone, email, or text (e.g., McLean et al, 2020).…”
Section: Increasing Availabilitymentioning
confidence: 99%